Factors associated with gender-based violence against women of the Esperanza Populated Centre, Huanuco - Leiva Yaro, Amalia (2019)
Objective. To describe the factors that are associated with gender-based violence. Methods. An observational, transversal, prospective and correlational research was carried out on a sample of 333  women from the esperanza populated centre, amarilis, Huanuco during the 2018 period. a scale was used in the data collection. the chi square test of independence was used in the inferential  analysis. Results. Overall, 81.7 % (272 women) reported mild violence, 12.3 % (41 women) moderate violence and 6% (20 women) severe violence. in addition, 6 %, 8.1 %, 9.9 % and 13.5 % of the women  experienced severe physical, psychological, sexual and economic violence, respectively. on the other hand, 8.4 % (28 women) were exposed to social factors, 5.4 % (18 women) to culural factors and 2.7  % (9 women) to personal factors. since social, cultural and personal factors are significantly associated with gender-based violence, all of them with p< 0.05. Conclusions. Social, cultural and  personal factors are associated with gender-based violence against women of the esperanza populated centre, Amarilis, Huanuco.